Laser-induced breakdown spectroscopy (LIBS) quality control and origin identification of handmade manufactured cigars - Alvira, Fernando Carlos (2015)
Tobacco is an agricultural product originating in America that is obtained by processing the leaves of various plants of the genus Nicotiana tabacum. It is the inedible product occupying the most plantings in the world, according to a recent report from the United Nations Food and Agriculture Organization. It is consumed in various ways, but the most popular form of consumption is, undoubtedly, by smoking cigarettes. A particular segment of the tobacco industry is the manufacturing of handmade cigars, which for some third-world countries is an important source of income. There are different qualities of cigars, and a major problem is the adulteration that occurs, for example, when authentic high-quality leaves are replaced by lower quality leaves. A factor that influences the quality of the cigars is the smoke combustion process, which depends on several factors, particularly the composition of the leaves. We present a simple and quick technique for the quality control and origin identification of handmade cigars that measures the Mg/Ca ratios in the tobacco leaves and wrappers of the cigars using laser-induced breakdown spectroscopy.